1998
DOI: 10.1136/oem.55.7.468
|View full text |Cite
|
Sign up to set email alerts
|

Cross sectional observation of the effects of carbon disulphide on arteriosclerosis in rayon manufacturing workers.

Abstract: Objective-A prospective cohort study was designed to clarify the relations between occupational exposure to carbon disulphide (CS 2 ) and its eVects on arteriosclerosis in workers in 11 Japanese rayon manufacturing factories. This report is a cross sectional baseline observation in the first study year. Methods-Study subjects were 432 male rayon workers (mean (range) age 35.5 (19.1-47.8); duration of exposure 13.4 (0.3-29.0)) and 402 male referent workers (age 35.8 (18.9-49.8)). Exposure to CS 2 was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 18 publications
(17 reference statements)
1
23
0
Order By: Relevance
“…Eleven of these had at least one major weakness (see Table 2). Three included data on potential covariates, but reported only crude results [7,39,47]. Four used matching in the construction of the study populations, but reported unmatched analyses with no explanation [4,9,10,51].…”
Section: Cardiac Risk Indicators and Low Exposures To Carbon Disulfidementioning
confidence: 98%
See 1 more Smart Citation
“…Eleven of these had at least one major weakness (see Table 2). Three included data on potential covariates, but reported only crude results [7,39,47]. Four used matching in the construction of the study populations, but reported unmatched analyses with no explanation [4,9,10,51].…”
Section: Cardiac Risk Indicators and Low Exposures To Carbon Disulfidementioning
confidence: 98%
“…Omae et al collected baseline information on a newly formed cohort of Japanese workers from 11 rayon factories [39] (Table 2). All study subjects were shift workers no more than 46 years old.…”
Section: Asiamentioning
confidence: 99%
“…Details of the recruitment were given in a previous paper 6) . Briefly, workers exposed to CS 2 consisted of all workers from seven rayon staple fiber factories and about half of the workers randomly selected from four rayon filament fiber factories.…”
Section: Study Base and Follow-upmentioning
confidence: 99%
“…It remains to be clarified whether or not the current CS 2 exposure level is low enough to prevent the occurrence of CS 2 -related health impairment and/or to ameliorate health effects due to previous high exposure. We therefore started a prospective cohort study with all Japanese rayon factories using sensitive indicators of subclinical health changes and detailed exposure assessment in 1992, and evaluated the study subjects' health comprehensively, including cardiovascular, cerebrovascular, opthalmological, neurological, neurobehavioral, and endocrinological aspects 6,7) . CS 2 effects on the endocrine system have also been observed, including effects on adrenal 8) , thyroid [9][10][11] , hypophysis 9,11) and gonad 12) function, whereas it has also been reported that there is no relationship between thyroid, hypophysis, and gonad function and exposure to CS 2 8, 13) .…”
mentioning
confidence: 99%
“…The questionnaires also included psychological tests evaluating the moods of subjects. The scales used were (v) the selfrated depression scale (SDS) and (vi) the manifest anxiety scale (MAS) 30) .…”
Section: Health Effect Assessment Subjective Symptom and Psychologicamentioning
confidence: 99%